2019
DOI: 10.1111/aogs.13750
|View full text |Cite
|
Sign up to set email alerts
|

The added benefit of transvaginal sonography in the clinical staging of cervical carcinoma

Abstract: Introduction Patients diagnosed with cervical cancer face several treatment options, depending on the physical examination and the imaging modality results. Transvaginal sonography (TVS) was proposed as an imaging option to determine local spread of cervical tumors, along with magnetic resonance imaging, also by recently released International Federation of Gynecology and Obstetrics recommendations. We examined whether combined data from physical examination, high‐detail TVS, and positron emission tomography w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Hence, VGS is more sensitive than MRI in identifying small lesions. Prior studies did not find that TVUS was better than MRI in the detection of lesions <2 cm [ 9 , 20 ]. Only one previous study showed that TRUS was superior to MRI in the identification of very small lesions (<1 cm) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, VGS is more sensitive than MRI in identifying small lesions. Prior studies did not find that TVUS was better than MRI in the detection of lesions <2 cm [ 9 , 20 ]. Only one previous study showed that TRUS was superior to MRI in the identification of very small lesions (<1 cm) [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the vaginal B-ultrasonography has a certain value on the early cervical cancer screening. MRI characterized by multi-level, multi-directional, multi-sequence imaging, with strong tissue resolution can be used for imaging staging of cervical cancer[ 13 ]. In this case, the MRI of the cervix showed a 3 cm diameter quasi-circular high T2WI signals in the anterior lip of the cervix and the anterior wall of the cervix, with limited diffusion and an ADC value of 0.838 × 10 -3 mm 2 /s, with a markedly enhanced edges during enhanced phrase.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a small subset of patients (n = 25) who underwent ultrasonography for preoperative local staging showed 100% concordance between ultrasound and histology after surgery for parametrial involvement. However, the mean maximal cervical lesion diameter was 1.6 cm, and the median age of patients was 44 years [37]. Thus, this cohort represents a highly selective set of candidates for surgical treatment in which parametrial involvement would be extremely rare.…”
Section: Parametriamentioning
confidence: 95%
“…Uterine corpus involvement was not evaluated in previous studies comparing ultrasound and MRI accuracy for staging cervical cancer [2,6,33,37]. Moreover, it has not been incorporated into the FIGO [26] or TNM [1] staging classifications.…”
Section: Uterine Corpus Involvementmentioning
confidence: 99%
See 1 more Smart Citation